Opposing outcomes of the industrial prison: Japan and the United States compared - Johnson, Elmer H. (International criminal justice review, 1994)
The industrial prison first emerged in the early 1820s as the Auburn system in New York State, combining the characteristics of the machine-based factory and the custodial prison. Unprecedented demands were placed on the skills and dedication of both prison staff and inmates. Political opposition gradually deprived the industrial prison of its early prominent place in American penology. In Japan, the model appeared later and today continues to flourish with easy access to the open market. Whereas the industrial prison and the contracting of prison labor suffered political attack in the United States, they are tolerated in Japan. Japanese prison personnel benefit from sound recruitment and a long history of in-service training. The American public debated whether priority was to be given to the rehabilitation of criminals or to the concept of the industrial prison, but in Japan, where the policy of diversion greatly reduces the proportion of offenders who end up in prison, and those who are imprisoned have been selected asbeing especially "unworthy," the industrial prison is seen as an appropriate means of managing such offenders